1986
DOI: 10.1128/iai.53.3.530-533.1986
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of the major outer membrane protein of Chlamydia trachomatis with murine monoclonal antibodies

Abstract: We prepared monoclonal antibodies against prototype strains of the 15 serovars of Chiamydia trachomatis and identified a subset of reagents that reacted with the major outer membrane protein(s) (MOMPs) of one or more serovars. We then determined the specificities of these anti-MOMP monoclonal antibodies by radioimmunoassay and immunoblot assays against the 15 serovars of C. trachomatis and a C. psittaci strain. We identified 14 different anti-MOMP antibody specificities, including serovar-, several orders of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Thus the hydrophobicity of the S3 residue might provide potential antibody-binding ability. The immunodominance of S3-VD IV observed in rabbits is probably different from that observed in mice, since the generation of species-reactive MAbs in mice is a rare event (3,20,26,28). Whether S3 is immunodominant or immunorecessive in humans is unknown at this time.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus the hydrophobicity of the S3 residue might provide potential antibody-binding ability. The immunodominance of S3-VD IV observed in rabbits is probably different from that observed in mice, since the generation of species-reactive MAbs in mice is a rare event (3,20,26,28). Whether S3 is immunodominant or immunorecessive in humans is unknown at this time.…”
Section: Discussionmentioning
confidence: 80%
“…It has functional roles for the structural integrity of the extracellular infectious elementary body (EB) and porin properties permitting uptake of essential nutrients such as ATP for the intracellular replicatory form, the reticulate body. Other studies (2,3,20,26,27,35,36,39) have demonstrated that the MOMP has discrete regions of antigenicity and immunoaccessibility. Comparative DNA analysis from MOMP genes of three different C. trachomatis serovars revealed that the MOMP has four regions of amino acid variability interspersed among five regions of amino acid conservation (27).…”
mentioning
confidence: 97%
“…The production of murine monoclonal antibodies 1A5 and F221/6C2/C2 has been described previously (3); these antibodies are specific for the major outer membrane proteins of serovars L2 and F, respectively. Antibody 47A2 was recovered following fusion of splenocytes from a BALB/c mouse that had been immunized with elementary bodies of strain L,/434/Bu to the SP2/0-Agl4 cell line as described previously (3). All antibodies were used as unfractionated ascites fluids.…”
Section: Methodsmentioning
confidence: 99%
“…As such it exhibits porin function under redox control [12] and its expression may be essential for EB to RB conversion following infection of the host cell. Antibodies raised to MOMP from C. trachomatis exhibited several different reactivities, revealing the presence of both type (serovar), subspecies, species and genus specific epitopes on the molecule [13,14]. Although C. psittaci and C. trachomatis share less than 10% DNA homology [15], dot blot analysis has revealed significant homology between the MOMP genes of the two species [16].…”
Section: Introductionmentioning
confidence: 99%